Assessment of the relationship between dental anxiety and oral health-related quality of life - Siraj D. A . A. Khan; Naif Mahdi Alqannass; Mohannad Mesfer Alwadei; Mazen Dhafer Alnajrani; Ziyad Mohammed Alshahrani; Ali Yahya Al Alhareth; Khalid Mohammed Alqahtani (Wolters Kluwer Medknow Publications, 2021)
Background: Dental anxiety and fear are the frequently encountered entities among most of the patients. The present study was conducted to assess the relationship between dental anxiety and quality of life (QoL). Materials and Methods: This study comprised of 118 patients. Dental trait anxiety (dental anxiety scale [DAS] and short version of the dental anxiety inventory [S-DAI]), Oral Health Impact Profile (OHIP-14), Decayed, Missing, and Filled Teeth (DMFT) score, and global assessment of functioning were recorded before and after treatment. Results: Out of 118 patients, males were 52 and females were 56. There was a correlation between both oral health ratings and DMFT (P < 0.001). OHIP-14 total score was significantly associated with both dental anxiety measures. DMFT shows significant association with dental anxiety and oral health-related QoL (OH-QoL) (P < 0.05). The mean DAS score before treatment was 17.3 and after treatment was 12.60, S-DAI score was 40.1 and 31.5 before and after treatment respectively, oral health status (patient rating) was 38.4 and 74.20 before and after treatment respectively, oral health status (dentist rating) was 38.7 and 73.1 before and after treatment respectively and aesthetics (dentist rating) was 35.6 and 72.4 before and after treatment respectively. There was improvement of OH-QoL with dental anxiety reduction which was significantly significant (P < 0.05). Conclusion: Authors found that there is correlation between dental anxiety and fear with the poor oral health-related oral hygiene.